OWNERSHIP CONCENTRATION ROLE ON BOARD DIVERSITY AND AUDIT COMMITTEE CHARACTERISTICS ON AUDIT QUALITY - Silvy Gresia; Iskandar Itan (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
This study aimed to analyze the relationship between board characteristics, audit committee meetings, and audit quality with ownership concentration as the moderating variable. This study used 133 firms in manufacturing sectors as the sample for the period 2016 to 2020. The results of the study show that the board’s age diversity has a negative significant effect on audit quality, board’s education, and number of audit committee meetings have a significant effect on audit quality. The findings also show that moderating variable could strengthen the relationship between board’s age diversity and audit quality and weaken the relationship between the number of audit committee meetings and audit quality.